Component-Controlled Synthesis of Gradient Electrode for Efficient Electrocatalytic Dye Decolorization. Issue 7 (1st January 2016) - Duan, Tigang; Chen, Ye; Wen, Qing; Duan, Ying; Qi, Lijuan
Abstract : We present the multi-pulse electrodeposition fabrication of gradient Pd-Sb-SnO2 on Ti substrate to improve the electrocatalytic performance of electrodes. Scanning electron microscopy (SEM) results show that pulse-deposited electrodes possess the morphology of flower-like clusters. The discussion for growth mechanism demonstrates that the production of flower-like cluster is related to the diffusion limitation. The difference between traditionally electrodeposited electrode and pulse electrodeposited electrode was investigated and demonstrated that pulse deposited electrode possesses a higher Sb 5+ /Sb 3+ ratio and higher Oads /Olat ratio. The electrochemical characterization shows that pulse deposited electrode has a significantly enhanced activity (98.57 ohm versus 362.7 ohm for electrochemical impedance). Moreover, the electrocatalytic dye decolorization experiments show that the morphology of flower-like clusters and the component gradient on pulse deposited electrode can provide more active specific surface area and advance the dye decolorization process (first-order kinetics constants: 24.2 × 10 −3 versus 9.19 × 10 −3 min −1 for methylene blue, 39.7 × 10 −3 versus 24.3 × 10 −3 min −1 for orange II and 51.7 × 10 −3 versus 24.2 × 10 −3 min −1 for methyl orange, respectively). These results demonstrate that the pulse electrodeposited electrode possesses more efficient catalytic activity. At last, we expect that the approach for electrode preparation can provide a chance to develop the methodology of component/morphology-controlled synthesis.